Algoma Central and Hudson Bay Railway diesel locomotives 170 and 171 - Swanberg, J. W. (Jack W.), 1939- (Creator) (1977)
Algoma Central and Hudson Bay Railway diesel locomotives GMD GP7 type No. 170 and GMD GP9 type No. 171 on local freight train at Oba, Ontario, Canada. Archives & Special Collections at the Thomas J. Dodd Research Center, University of Connecticut Library J.W. Swanberg Papers